KONTRUKSI KULTUR HISTORIS DALAM FOLKLOR NDILKORO DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA DAN SASTRA - Tri Widiastutik; Moh. Ahsan Shohifur Rizal (Jurnal Tinta, 2021)
Folklore is a traditional culture that is owned by a certain group and its distribution is hereditary. Spread from generation to generation shows that there is an oral culture inherited from our ancestors. Folklore as a stand-alone science in Indonesia needs intensive research and development so that the cultural results of our ancestors will not disappear and can be taken advantage of. The method used by researchers in this study is to use qualitative research types that are library research. In this study, researchers collected data using a descriptive form of analysis. Descriptive analysis method is used to describe the facts which are then analyzed. The reason for using this method is because the way this research method works can describe events and objects as historical facts to determine the role of folklore legend Ndhilkoro in Bantur District. While the approach used in this study uses an anthropolinguistic approach based on research on a culture. The focus of research is emphasized in the analysis of: 1) Construction of historical culture in the Ndhilkoro folklore. 2) Study of extrinsicisation of oral literature and its implications in learning Indonesian language and literature. Analysis is done by combining functionalist concepts with the reality of social life. The findings in this study are in the form of Ndhilkoro folklore which contains social values, so that they can be used as teaching materials for the 2013 curriculum for high school grades X in KD 3.7 through KD 3.9 on local wisdom of local folklore.